THE SIGNIFICANCE OF TEACHERS' LEARNING MANAGEMENT SKILLS FOR SUCCESSFULL EARLY CHILDHOOD EDUCATION - Dessy Putri Wahyuningtyas; Najamuddin Petta Solong; Nurmadina HS; Arkam Lahiya; Mas'ud Muhammadiah (Sean Institute, 2023)
Effective learning management skills can assist teachers in achieving the objectives of early childhood education, namely the optimal development of children's potential. Learning in early childhood is a child-oriented learning activity that is suited to the age level of the child a number of learning experiences through play produced by the educator by providing the material (content) and learning process. Teachers play a crucial role in determining the effectiveness of early childhood education. Consequently, it is essential to recognize the learning management skills that educators possess. Consequently, the goal of the research is to analyze the role of learning management in assisting instructors to foster a creative and innovative learning environment and its implications for the classroom learning process. The research approach is a literature review or literature review conducted by examining journals and other references that pertain to the implementation and use of learning management in early childhood education. The results indicated that in implementing learning management, the teacher's role in mastering learning management skills is crucial, and that there is an effect when learning management is applied due to the need for techniques in implementing learning management so that the classroom environment remains conducive and the learning process is maximized. The implication of the study is that, with good learning management, learning objectives can be attained more efficiently and effectively, hence enhancing students' learning outcomes.